Karakteristik Metode Simā’an Santri Pada Program Tahfīzh Pesantren Modern Datok Sulaiman Putra - Teguh Arafah Julianto; Rukman Abdul Rahman Said; Fauzan Dzawilhaj Anzar (Institut Agama Islam Negeri Palopo, 2022)
This study discusses the Simā'an Method of Santri in the tahfīzh Program of Modern Islamic Boarding School. This study aims to determine the characteristics, implications and supporting and inhibiting factors of the simā'an method of students in the tahfīzh program of Modern Islamic Boarding School Datok Sulaiman Putra Palopo City. The type of research used in this study is qualitative. The results of this study show that 1) There are 3 characteristics of the simā'an method of students, namely Simā'an Mukammal, Simā'an Tasmi and Tasyakuran Simā'an sugro 30 juz. 2) The application of the simā'an method has a positive impact on the memorization process, students can murāja'ah and increase the constancy of the students' memorization. 3) The existence of facilities is supported for simā'an activities, there is an increase in the motivation and enthusiasm for reciting the students, maintaining the consistency of togetherness between students, improving the quality of the students' recitation of the Qur'an and becoming a place for mental training of students. Busyness in school learning activities or assignments, as well as the existence of memorized readings that are less than optimal and students are also still less focused when simā'an has taken place to be an inhibiting factor.